2019
DOI: 10.1021/acs.biomac.9b01437
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Adhesion of Different Cell Types Modulated by Thermoresponsive Polymer Brush Thickness

Abstract: Tunable adhesion of different cell types on well-defined surfaces has attracted common interests in the field of biomaterial science and surface engineering. Herein, we demonstrate a new strategy for the regulation of cell adhesion by simply controlling the thickness of thermoresponsive poly(N-isopropylacrylamide) (PNIPAAm) brushes via surface-initiated atom transfer radical polymerization (ATRP). The adhesion of different cell types (4T1, HEK293, H9C2, HUVEC, and L929) can be easily modulated by varying the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…It was reported that the hydrophobicity of pNIPAM could affect the adhesion of cells of different origins due to its capacity to adsorb matrix proteins (i.e., fibronectin) and growth factors stimulating cell growth [ 48 ]. The dependence of cell behavior on the type of cell line used in biological experiments evaluating pNIPAM copolymer was also reported by others [ 33 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 73%
“…It was reported that the hydrophobicity of pNIPAM could affect the adhesion of cells of different origins due to its capacity to adsorb matrix proteins (i.e., fibronectin) and growth factors stimulating cell growth [ 48 ]. The dependence of cell behavior on the type of cell line used in biological experiments evaluating pNIPAM copolymer was also reported by others [ 33 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 73%
“…Next, 100 µL of the resultant suspensions of reverse micelles (RM 2 ) or normal micelles (NM 2 ) was spin‐coated on a microscope cover slide (Assistant, Germany) and dried in open air before subjected to AFM in “ScanAsyst in air” mode, as described in earlier work. [ 31 ] The dynamic diameters of RMs in THF and NMs in water were determined by using dynamic light scattering nanosizer (Malvern Nano‐ZS90) equipped with organic solvent resistant cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…The well-defined polymer brush surfaces are also an important class of cell culture platforms because cellular adhesion is affected by the surface properties of materials, including wettability, charge density, chemical functionality, and thickness. 72–75 Initial cellular adhesion has been evaluated on various types of polymer brushes such as zwitterionic PMPC, cationic poly(2-methacryloyloxyethyl trimethylammonium chloride) (PMTAC), anionic poly(potassium 3-(methacryloyloxy)propyl sulfonate) (PSPMA), non-ionic PHEMA, and poly(2,2,2-trifluoroethyl methacrylate) (PTFEMA). 74 The number and morphology of adherent human cervical adenocarcinoma epithelial cells were clearly dependent on the surface ζ -potentials as a parameter of charge density, while no significant correlation was observed with respect to the hydrophilic/hydrophobic nature of the substrate.…”
Section: Polymer Brush-based Biointerfacesmentioning
confidence: 99%